Hydrodynamic Performance Assessment of Straight and Helical Hydrokinetic Turbine Hydrofoil-Blade Sections in River Oyun, North-Central Nigeria - Ladokun, Laniyi Laniran (Mekanika: Majalah Ilmiah Mekanika, 2024)
The performance of lift-based hydrokinetic rotor turbines usually depends on the blade sections or hydrofoil profile. Different hydrofoil blade sections, having different profiles and geometries, give different coefficients of performance in different hydrodynamic settings. This study examined the influence of blade geometry on the power stage characterization of vertical axis crossflow hydrokinetic turbines under conditions of low river current velocity. Two turbines have been selected to characterize the power stage. Pre-developed straight-bladed National Advisory Committee for Aeronautics (NACA) 0021 hydrofoil blade sections and a Gorlov helical/curved NACA 0021 pattern were used in the hydrodynamic experimental characterization along River Oyun, Kwara State, North-Central Nigeria. The graphical ratio of the coefficient of performance, CP,which measures the efficiency of the turbine blade sections converting kinetic energy into mechanical energy, and the turbine blade Tip Speed Ratio (TSR), was used to analyze the hydrodynamic blade performance characterization. The peak CP values, the optimal TSR, the CP curve shape, and the stall regions from the CP-TSR chart were used to determine the hydrofoil with optimal performance.